Primer of Freudian psychology - Hall, Calvin S. (Mentor New YorkUS, 1982)
Chronicles the highlights of Sigmund Freud's life; and outlines his thinking on the organization, dynamics and development of the normal human personality. Includes topics such as: the instincts, anxiety, repression, defence mechanisms, fixation, regression, and the development of the sexual instinct.